Secrecy performance by power splitting in cooperative dual-hop relay wireless energy harvesting - Yang, Shouyi; Sehito, Nabila; Abbasi, Muhammad Inam; Al Harbi, Abdullh G.; Khan, Muhammad Abbas; Khan, Muhammad Amir; Kamal, Mian Muhammad (2022)
In wireless communication systems, for secure communication between a transmitter and receiver over the communication channel, the physical layer security is widely utilized. The paper presents a dual-hop wireless full-duplex relay (FDR) network with a source relay and destination relay between two nodes and listening devices. The relay and source use energy harvesting to gain energy from power beacon. Two cooperative techniques are utilized to investigate the amplify-forward (AF) and decode-forward (DF) secrecy capacity in the energy harvesting power splitting system. It is shown that the secrecy performance of an AF relay is better than the secrecy performance of a DF relay in the given form. At 40-meter distance between the relay and the eavesdropper in an energy harvesting system, the AF relay outperforms the DF relay. The simulation is performed using the Monte-Carlo method in MATLAB.